2021
DOI: 10.34172/jpe.2021.15
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and acute kidney injury presentation; stages and prognosis

Abstract: Introduction: Coronavirus disease 2019 (COVID-19) can present with acute kidney injury (AKI). Although the rate of AKI among these patients is not high, their outcome could be much worse than the other patients. Serum creatinine rise along with other laboratory findings may help as a clinical predictor of COVID-19 disease prognosis. Objectives: We aimed to evaluate the incidence and possible predictors of AKI occurrence and its outcome during the COVID-19 pandemic. Patients and Methods: In a retrospective obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…There can be gender and racial disparities of AKI in COVID-19 patients as described previously, [ 24 ] however, we did not take racial differences into account as most of our study participants were from South Asian locality, but gender had no predisposition to AKI in our cohort. On the contrary, Soheili et al [ 25 ] found females more prone to AKI in their cohort of 946 patients. In another cohort, the mortality rate of COVID-19 patients with AKI was exceeding 56%.…”
Section: Discussionmentioning
confidence: 91%
“…There can be gender and racial disparities of AKI in COVID-19 patients as described previously, [ 24 ] however, we did not take racial differences into account as most of our study participants were from South Asian locality, but gender had no predisposition to AKI in our cohort. On the contrary, Soheili et al [ 25 ] found females more prone to AKI in their cohort of 946 patients. In another cohort, the mortality rate of COVID-19 patients with AKI was exceeding 56%.…”
Section: Discussionmentioning
confidence: 91%